Impact of Alkaline Immersion Time on Nano-Hydroxyapatite Synthesis from Broiler Eggshells with Electrochemical Method Using Constant Direct Current (CDC) - Asep Muhamad Samsudin; Tutuk Djoko Kusworo; Hana Nikma Ulya; Muhammad Akhsanil Auladi (Jurnal Kimia Sains dan Aplikasi, 2023)
Calcium phosphate is widely used in biomaterials, especially as a bone substitute. One of the calcium phosphate compounds that is widely used is hydroxyapatite. In biomedical applications, nano-sized hydroxyapatite particles have better bioactivity than coarse crystals. Hydroxyapatite can be synthesized from various sources of calcium and phosphate. Broiler eggshells were chosen as a source of calcium in this study because they have a relatively high calcium content. The method used in the synthesis of nano-hydroxyapatite in this research is the electrochemical method. This research aims to examine the effect of varying NaOH immersion time on the size and structure of calcium phosphate particles produced using an electrochemical method made from chicken egg shells. The synthesis of nano-hydroxyapatite from chicken egg shells was carried out in 4 stages: material preparation, electrolysis, precipitate immersion, and characterization. Nanometer-sized particles can be acquired through an immersion process lasting at least four hours, and it is observed that the longer the duration of immersion, the greater the resemblance of the resulting structure to hydroxyapatite.